Phacoemulsification versus Laser Peripheral Iridotomy for Treating Primary Angle Closure Glaucoma: A Systematic Review and Meta-Analysis - Sharif RK; Aljahdali FF; Aljabri HM; Alomari LK; Sagim RA; Alamri DM; Alshehri MA; Alshigari RA (Clinical Ophthalmology, 2024)
Rahaf K Sharif,1 Faisal F Aljahdali,1 Hind M Aljabri,1 Lugean K Alomari,1 Renad A Sagim,1 Duaa M Alamri,1 Merai A Alshehri,2 Rayan Abdullah Alshigari3 1College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 2Department of Surgery, College of Medicine, University of Bisha, Bisha, Saudi Arabia; 3Department of Glaucoma Section, King Khaled Eye Specialist Hospital, Riyadh, Saudi ArabiaCorrespondence: Faisal F Aljahdali, College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia, Email faisalfahadaljahdali@gmail.comBackground: Primary Angle Closure Glaucoma (PACG), is caused by narrowing the iridocorneal angle and increases the risk of blockage in the trabecular meshwork. Phacoemulsification and laser peripheral iridotomy (LPI) effectively control IOP elevation and widen the angle. This systematic review and meta-analysis compared Phacoemulsification and LPI Effectiveness for PACG.Methods: We searched Medline, Embase, and CENTRAL. We included randomized controlled trials (RCTs) that compared Phacoemulsification and LPI for individuals with PACG. We sought to evaluate the following outcomes: mean IOP, number of glaucoma medications, visual acuity (VA), visual field (VF) progression, peripheral anterior synechiae (PAS), Shaffer gonioscopy grading, central corneal thickness (CCT), central endothelial cell density (CECD), and poor response to surgery. The standardized mean difference (SMD) was used to represent continuous outcomes, while the risk ratio (RR) was used to represent dichotomous outcomes.Results: 5 RCTs that enrolled 917 participants were deemed eligible. The phacoemulsification group showed statistically significance lower mean CCT and CECD and lower risk of poor response to surgery compared to LPI (SMD = − 1.10; 95% − 1.50, − 0.70; P< 0.001, SMD − 366.12; 95% − 652.59, − 79.65; P=0.01, and RR 0.35; 95% 0.23, 0.54; P< 0.001 respectively). There were no significant improvement in IOP and number of medications between both groups (SMD = − 0.74; 95% CI = − 2.26, 0.78; P=0.34, and SMD − 17.58; 95% CI = − 50.28, 15.12; P=0.29 respectively). Finally, there were also no significant differences in VA, VF progression, PAS, and mean Shaffer gonioscopy grading between both groups.Conclusion: Phacoemulsification showed statistically significant lower mean corneal thickness, central endothelial cell density, and lower risk of poor response to surgery compared to LPI. However, there were no significant differences in mean IOP, number of medications, VA, VF progression, PAS, and mean Shaffer gonioscopy grading between Phacoemulsification and LPI.Keywords: phacoemulsification, laser, iridotomy, glaucoma